2021
DOI: 10.4236/ojapps.2021.111006
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the Knowledge, Attitudes and Practices of the Populations on Cholera in Benin

Abstract: Cholera is a disease that Benin has been fighting against for years but which continues to create economic losses for households. The aim of this study is to assess the level of knowledge of the population about this disease and to assess hygiene practices in order to identify the factors responsible for its sustainability. The data were collected through a survey of 720 households in the 12 departments of the country. These data were analyzed with SAS software and three groups of people were identified on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In the absence of previously validated scales regarding the studied concepts, questions regarding knowledge, attitude, and practices were developed based on previous studies [17][18][19][20][21][22][23]; additional questions were added when deemed necessary. The KAP scales were adopted since it has been suggested that cholera prevention, control, and management directly depend on individual and community sanitation knowledge, behaviors, attitudes, and practices.…”
Section: Scale-based Variablesmentioning
confidence: 99%
“…In the absence of previously validated scales regarding the studied concepts, questions regarding knowledge, attitude, and practices were developed based on previous studies [17][18][19][20][21][22][23]; additional questions were added when deemed necessary. The KAP scales were adopted since it has been suggested that cholera prevention, control, and management directly depend on individual and community sanitation knowledge, behaviors, attitudes, and practices.…”
Section: Scale-based Variablesmentioning
confidence: 99%